Optimization of exercise execution technique to maximize power training induces changes - Alberti, G.; Ferrari Bravo, D.; Silvaggi, N. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction Training programs of power athletes usually include dynamic exercises, such as squat jumps with (CMJ) or without countermovement (SJ), aimed to enhance muscular power. To optimize this training regime, the resistance that maximize the mechanical power is used and it was reported to range from 47 to 59 % of 1 repetition maximum (RM) in strength trained athletes (Baker et al., 2001). However, the use of heavy load could increase the stress on the musculoskeletal system, rising the risk of injuries or overuse damage. The selection of the overload should take into account the execution technique of the exercise so that the minimal load, that allows high mechanical power to be reached, can be identified. In particular, during countermovement squat jumps, maximizing the velocity of the descent, higher force production can be obtained in the following concentric phase using the same overload, (see figure 1, unpublished results). The aim of this study was to verify if manipulating the execution technique of the squat jumps is possible to induce higher improvement of strength and power compared to subjects that use traditional not modified technique. Methods Twenty volleyball players (10 male and 10 female) with experience of resistance training were randomly assigned to an experimental training group (EXP) and to a control group (CON). The training program of the two groups consisted in 6x6RM half-squats and 5x6RM using the contrast method, i.e. alternation of sets of half squats at 80% of 1RM and jump squats at 40 % of 1RM (Duthie et al., 2002). The squat jump technique during the contrast method of EXP group was modified asking the athletes 1) to descent as quick as possible, resulting in a loss of contact with the ground, 2) stop the movement in the shorter time as possible at a knee angle of 90°, and 3) to maximally accelerate during the concentric phase. Half-squat maximal strength (1RM), squat jump (SJ) and countermovement jump (CMJ) were measured before and after 8 weeks of training. Data were analyzed using a three-way ANOVA (gender x group x time) followed by Tuckey`s post hoc test. Results The results of pre and post training test are presented in Table 1 and Figure 1. Gender differences were found in all the strength variables measured. No gender x time interaction was found, while group x time interaction was significant (p<0.001) Discussion/Conclusions This study showed that optimizing and modifying the execution technique of jump squat is possible to maximize the induced changes of power training. In other words, it is possible to maximize the resistance training effect not only manipulating the overload, but also modifying the execution technique of exercise traditionally used by the athletes. In the present investigation, the EXP group showed higher improvement than the CON group. However, as these athletes were used to the traditional execution technique of the jump squat, it cannot be excluded that the higher improvements were determined by the change of training stimulus itself, more than by the higher mechanical power reached in the concentric phase. However, based on our results, we suggest coaches to pay more attention on the execution technique of exercises and not only on the external overloads modulation.